Menghadapi Kemacetan: StudiFenomenologis tentang PengalamanPengendara Motor di Jalan Ketintang,SurabayaLAM MENGHADAPI KEMACETAN DI SURABAYA, KETINTANG - Rakha Ammar Thoriq (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2024)
This study aims to understand the subjective experiences of motorcyclists in dealing with traffic congestion on Jalan Ketintang, Surabaya. Congestion in this area has worsened due to the increasing number of vehicles, the lack of adequate transportation infrastructure, and the presence of poorly maintained railway crossings. Using a phenomenological approach, the research explores the dynamics of social interactions among motorcyclists and other road users, as well as the factors influencing rider behavior when caught in traffic jams. Data were collected through in-depth interviews and observations of motorcyclists who regularly pass through the area. The findings are expected to contribute theoretically to social science studies, particularly in understanding behavior in crowded public spaces. In addition, the study aims to provide practical recommendations for improving traffic conditions and fostering collective awareness of the impact of congestion on the quality of life. This research also explores the adaptive strategies developed by motorcyclists in response to everyday traffic congestion.